2019
DOI: 10.1111/tct.13078
|View full text |Cite
|
Sign up to set email alerts
|

Navigating medical culture and LGBTQ identity

Abstract: Background:Contextualised within minority stress theory, this study explores the experiences of lesbian, gay, bisexual, transgender, and queer (LGBTQ) medical students and how they navigate medical school as sexual minorities. Past research indicates many LGBTQ medical students have witnessed medical school staff make prejudice comments about LGBTQ patients, leading sexual minority students to suppress LGBTQ identities and experience adverse mental health outcomes. Methods: Focus groups were conducted with 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
26
0
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 8 publications
2
26
0
8
Order By: Relevance
“…The ‘safety’ of these environments influences identity disclosure, residency choice and even career path 3 . This is in keeping with other studies that show that many LGBTQ residents hide their sexual identity due to fears that it will impact recruitment or partnership opportunities 4 . LGBTQ trainees in several studies indicated that access to ‘out’ LGBTQ faculty mentors and role models would have improved their training experience 3,4 …”
supporting
confidence: 82%
“…The ‘safety’ of these environments influences identity disclosure, residency choice and even career path 3 . This is in keeping with other studies that show that many LGBTQ residents hide their sexual identity due to fears that it will impact recruitment or partnership opportunities 4 . LGBTQ trainees in several studies indicated that access to ‘out’ LGBTQ faculty mentors and role models would have improved their training experience 3,4 …”
supporting
confidence: 82%
“…Yet many medical students do not utilize these services, especially underrepresented minority students such as African American students 2 . One reason is that all medical students’ knowledge of campus support services is limited 3 .…”
Section: Acknowledge the Why: Failure Of Systemic Supportmentioning
confidence: 99%
“…A larger issue is that more than two thirds of medical students do not seek help from their faculty or peers for stress, emotional struggles, or academic problems. They perceive a stigma attached to seeking help and worry that it could negatively impact their medical school and career trajectories, preferring instead to seek help from friends and family 2,3 . They fear judgment from supervisors and experience shame when asking for help 4 .…”
Section: Acknowledge the Why: Failure Of Systemic Supportmentioning
confidence: 99%
“…22 Some studies have also shown that LGBTQ medical students, trainees, and physicians are likely to witness derogatory comments, substandard care, or refusal of care towards LGBTQ patients, which was also seen in our cohort. 22,27 These barriers impede trainees' abilities to fully engage in their work and achieve a sense of accomplishment, thereby inhibiting their ability to ourish in their environment. This is best illustrated by our study nding only 0.1% of trainees who identi ed as LGBTQ were willing to mentor LGBTQ individuals, suggesting individuals may not be able to dedicate themselves to something or someone for the greater good.…”
Section: Barriers In the Workplace (Engagement And Accomplishment)mentioning
confidence: 99%
“…These experiences, whether positive or negative, can be compounded in individuals who identify with multiple URiM groups (e.g., Black and Gay, Native American and Lesbian, Latino and Transgender, etc.). 27…”
Section: Intersectionalities (Positive Emotion Engagement and Accomplishment)mentioning
confidence: 99%